Land Takeover by the Medan City Government: Evaluation of the Conflict Resolution Process in the Jalan Nibung Raya Hgb Case - JE Melky Purba; Tanjung, Indra Utama; Poppy Oktaviona (International Journal of Synergy in Law, Criminal, and Justice, 2024)
Expropriation of land by the government often results in conflict, especially when it impacts existing Building Use Rights (HGB) holders. In Medan City, the Jalan Nibung Raya case is a significant example of how land expropriation policies can affect local communities. This research aims to evaluate the process and results of land expropriation by PEMKO Medan, in particular its impact on HGB holders and the effectiveness of the conflict resolution mechanisms adopted. This research uses qualitative methods to collect and analyze data. Primary data was collected through in-depth interviews with affected HGB holders, government officials and land experts. Field observations and document analysis are also used to understand the policy context and community responses. This analysis makes it possible to assess the effectiveness of the land expropriation process and existing conflict resolution mechanisms. The research results show that the land takeover process by PEMKO Medan did not involve relevant stakeholders, which led to resistance and legal conflicts. Many citizens feel deprived of their rights without adequate compensation or solutions. A lack of transparency and communication between the government and citizens exacerbates the situation, increasing tensions and distrust between parties. Keywords :Land Takeover, Land Conflict, Building Use Rights, PEMKO Medan, Jalan Nibung Raya